Pertanggungjawaban Terhadap Tindak Pidana Pencemaran Lingkungan Hidup - I Made Aditya Dwipayana; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
Environmental damage in Indonesia is increasingly worrisome, even endangering every living creature, including future generations of life. In an effort to protect the environment in Indonesia, the government has issued Law No. 32 of 2009 concerning Environmental Protection and Management, which in principle follows the principle of the Strict Liability of the environment and how it is resolved. From the background, the problem can be formulated as follows: 1. what is the responsibility of criminal acts against environmental pollution? 2. How is the law applied to environmental pollution crime? The research method used is to use normative research. Legal materials used are primary legal material and secondary law. After all the materials collected are then processed using deductive logic and analysis of legal interpretation. Environmental pollution is a change in the environment that is not desirable because it can affect the activities, health and safety of living things. And it can be concluded as follows, the responsible parties are not only individuals, but also corporations, for example a business entity. Where the application of the law regarding environmental pollution crimes is is generally contained in laws and regulations relating to protection and management of the environment. It is suggested that the government be more assertive in demanding accountability for environmental pollution.